THE ROLE OF PEER SOCIAL SUPPORT AND LONELINESS IN PREDICTING ONLINE GAMING ADDICTION AMONG ELEMENTARY SCHOOL CHILDREN - Haris Herdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The advancement of digital technology has led to a significant increase in online game usage among elementary school children. While gaming may offer certain cognitive and emotional benefits, excessive use poses a risk of addiction, which can negatively impact children's academic, social, and psychological well-being. This study aims to examine the role of peer social support and loneliness in predicting online gaming addiction among elementary school students. Employing a quantitative approach with a causal-comparative method, the study involved 62 students from grades IV to VI in Bekasi Regency and Municipality, selected through random sampling based on criteria for online gaming addiction. Data were collected using three psychological scales, each validated and tested for reliability. Data analysis was conducted using multiple linear regression, preceded by classical assumption tests. The results revealed that neither peer social support nor loneliness, whether individually or jointly, significantly predicted online gaming addiction. These findings suggest that online gaming addiction in elementary-aged children cannot be explained solely by psychosocial factors, but must also consider other elements such as parental supervision, self-control, and game design features. The study highlights the need for more comprehensive and context-based intervention strategies tailored to children's environments.